Phygitalization of educational technologies in Russia: directions, examples, problems - Andrey I. Kapterev (RUDN Journal of Informatization in Education)
Problem statement . The modern social and communicative situation requires fundamental changes in didactic models, educational engineering and pedagogical design. The Russian experience has certain specifics in the digital transformation of vocational education. A few years ago, a new trend appeared in the world - the restructuring of educational technologies (EdTech) in the direction of phygitalization. At the junction of the digital and physical worlds, in 2013, such a concept as digital technologies was born. Phygital (physical + digital) is a complex of technologies where students get a unique interactive experience using both traditional material sources of educational information and virtual communication in the educational process. The emergence of such a phenomenon as phygitalization is due to the fact that the boundaries between the physical and digital are becoming increasingly blurred, which opens up new opportunities for socialization and professionalization (including in the higher education system). This area of educational activity is considered a priority and basic direction of the transformation of Russian education. Within the framework of this direction, the main attention is paid to the following aspects: (a) the use of Internet resources for pedagogical purposes, (b) the structuring of the curriculum in accordance with the modular principle, (c) an increase in the amount of study time for solving practical problems, (d) presentation of knowledge in accordance with the level of success of passing the previous blocks of educational information by each student (individual learning paths), (e) evaluation of the effectiveness of learning outcomes. The purpose of the study is to briefly, but, if possible, fully describe the methodological, theoretical and technological foundations of the phygitalization of educational technologies. Methodology . Such inter-scientific approaches as system-structural, system-activity, and pedagogical competence approach were used. A content analysis and thematic monitoring of the implementation of phygitalization in universities was carried out. Results. 1) The main directions of phygitalization of educational technologies are analyzed: a) use of teachers’ personal websites, b) the development of virtual laboratories, c) the use of generative language models of artificial intelligence.; 2) the importance of each component is analyzed and examples of how they can be implemented in practice are given, the main problems are discussed and potential solutions are proposed; 3) an overview of the main functions of the phygitalization of educational technologies is presented, including the definition of this trend, characteristics and main problems; 4) the main methods and tools used in the phygitalization of educational technologies are discussed; 5) the most promising areas of research in this field are determined. Conclusion . The phygitalization of educational technologies at universities has the potential to increase the subjectivity of vocational education by providing students with individual learning trajectories and a much more exciting learning experience.